Analisis Pemberdayaan Peran dan Fungsi Camat - KHAIRI, AKMAL (UI Scholars Hub, 2011)
. The legal foundation change on the local governance affects the change of status, role, and function of the sub-district’s head. In the past a sub-district’s head is the person in full charge of an area, however now he is only part of local apparatuses who get his authority if there is a delegation from the Regent/Mayor. To increase the role of the sub-district head in its area, the local government of Depok did some empowerment efforts. The research aims to analyze the sub-district head empowerment done by the local government of Depok by doing case study in three sub-districts in Depok, i.e. Beji, Sukmajaya, and Pancoran Mas. The paradigm of the research is positivistic with qualitative technique of data collecting thorugh in-depth interview and literature study. The result of the research shows that the empowerment done by the local government of Depok is not optimal. The sub-district organization is merely considered complimentary, therefore has les strategic authority.